Integrasi Syara’ dan Ade’ dalam Tradisi Pernikahan Bugis Bone Sulawesi Selatan - Djawas, Mursyid; Ridhwan, Ridhwan; Yusof , Wafaa'; Said, Wardana; Nadhiran, Hedhri (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
This study seeks to examine the incorporation of Islamic and customary law into the marriage customs of the Bugis Bone community in South Sulawesi. This research is an empirical legal study employing a legal history and legal sociology methodology. The data for this study was generated from studies of relevant literature and in-depth interviews. This study suggests that syara' and ade' are integrated in the Bugis marital tradition, as evidenced by sompa or dowry, tudang penni, mappacci and mabbarazanji, mappanre tame, and assitulung-tulungan or ma'jama (helpng each other or work collaboratively). If you are referring to the study of Islamic law, then this tradition is part of al-urf, which does not contradict the Qur'an, Sunnah, or good practices, and can be adopted because it provides benefits and advantages. The diverse marriage rituals practiced by the Bugis Bone group are the consequence of the fusion of Islamic and customary law that has occurred throughout the course of the community's history. Because Islamic law, being the most essential component of Islamic teachings, cannot be divorced from society's norms, which have become living law. This fact also constitutes a scientific argument that refutes the receptie theory advanced by earlier experts. From the perspective of Islamic law, the marriage tradition of the Bugis Bone group revealed a harmonious combination of Islamic and customary law. Similarly, sociologically, this integration is able to create rules that control and help achieve harmony and mutual benefit.